Influence of Infant Cleft Dimensions on Velopharyngeal Function in 5-Year-Old Danish Children Born With Unilateral Cleft Lip and Palate. (April 2020) - Botticelli, Susanna; Küseler, Annelise; Mølsted, Kirsten; Andersen, Helene Soegaard; Boers, Maria; Shoeps, Antje; Emborg, Berit Kildegaard; Kisling-Møller, Mia; Pedersen, Thomas Klit; Andersen, Mikael; Willadsen, Elisabeth
Aim: To examine the association of cleft severity at infancy and velopharyngeal competence in preschool children with unilateral cleft lip and palate operated with early or delayed hard palate repair. Design: Subgroup analysis within a multicenter randomized controlled trial of primary surgery (Scandcleft). Setting: Tertiary health care. One surgical center. Patients and Methods: One hundred twenty-five infants received cheilo-rhinoplasty and soft palate repair at age 3 to 4 months and were randomized to hard palate closure at age 12 or 36 months. Cleft size and cleft morphology were measured 3 dimensionally on digital models, obtained by laser surface scanning of preoperative plaster models (mean age: 1.8 months). Main outcome measurements: Velopharyngeal competence (VPC) and hypernasality assessed from a naming test (VPC-Sum) and connected speech (VPC-Rate). In both scales, higher scores indicated a more severe velopharyngeal insufficiency. Results: No difference between surgical groups was shown. A low positive correlation was found between posterior cleft width and VPC-Rate (Spearman = .23; P = .025). The role of the covariate "cleft size at tuberosity level" was confirmed in an ordinal logistic regression model (odds ratio [OR] = 1.17; 95% confidence interval [CI]:1.01-1.35). A low negative correlation was shown between anteroposterior palatal length and VPC-Sum (Spearman = −.27; P = .004) and confirmed by the pooled scores VPC-Pooled (OR = 0.82; 95% CI: 0.69-0.98) and VPC-Dichotomic (OR = 0.82; 95% CI: 0.68-0.99). Conclusions: Posterior cleft dimensions can be a modest indicator for the prognosis of velopharyngeal function at age 5 years, when the soft palate is closed first, independently on the timing of hard palate repair. Antero-posterior palatal length seems to protect from velopharyngeal insufficiency and hypernasality. However, the association found was significant but low.